DMOC-based robot trajectory optimization with analytical first-order information - Villanueva-Pinon, Carla; Arechavaleta, Gustavo (Zielona Góra: Uniwersytet Zielonogórski)
Discrete mechanics and optimal control (DMOC) is a numerical optimal control framework capable of solving robot trajectory optimization problems. This framework has advantages over other direct collocation and multiple-shooting schemes. In particular, it works with a reduced number of decision variables due to the use of the forced discrete Euler-Lagrange (DEL) equation. Also, the transcription mechanism inherits the numerical benefits of variational integrators (i.e., momentum and energy conservation over a long time horizon with large time steps).
Keywords: discrete mechanics and optimal control; variational integrators; humanoid robot motions